2018
DOI: 10.18203/2320-1770.ijrcog20183780
|View full text |Cite
|
Sign up to set email alerts
|

Significance of transvaginal sonographic assessment of cervical length before induction of labour

Abstract: Background: The traditional method of predicting whether an induced labor will result in successful vaginal delivery is based on pre-induction favourability of cervix as assessed by bishop score. However, this method is limited by subjectivity and reproducibility and though done in all the patients prior to induction of labour, several studies have demonstrated poor correlation between Bishop score and outcome of labor. Currently assessment of cervical status by sonographically at term in induction of labor is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…6,15 Alalfy et al, Shreya et al and Mohamed El Bishry et al concluded in their studies that sonographic evaluation of the cervix was better than Bishop's score in predicting outcome of the induction. 7,10,18 On the other hand, Khandelwal et al and Chandra et al concluded that Bishop's score was superior to the sonographic parameters. 19,20 The differences may be due to the fact that all the above mentioned studies included women with post dated pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…6,15 Alalfy et al, Shreya et al and Mohamed El Bishry et al concluded in their studies that sonographic evaluation of the cervix was better than Bishop's score in predicting outcome of the induction. 7,10,18 On the other hand, Khandelwal et al and Chandra et al concluded that Bishop's score was superior to the sonographic parameters. 19,20 The differences may be due to the fact that all the above mentioned studies included women with post dated pregnancy.…”
Section: Discussionmentioning
confidence: 99%